Growth Performance and Cultivation of Four Oyster Mushroom Species on Sawdust and Rice Bran Substrates - Owaid, Mustafa Nadhim (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2015)
Pleurotus species are progressively becoming important edible mushrooms worldwide and it is of importance in choosing suitable substrates in a given place to grow them. The study provides basic and valuable information on mycelial growth rates and yield efficacy of four different Pleurotus spp. The highest average mycelium growth of 1.29 mm/day followed by 1.17 mm/day was observed in the bags of P. salmoneostramineus and P. ostreatus grey, respectively. Similarly, the highest cumulative growth of 12.90 cm/day and 11.74 cm/day was recorded in the 30 day old bags of P. salmoneostramineus and P. ostreatus grey, respectively. There was a significant increase (P < 0.05) of about three fold in the pin head formation of P. ostreatus grey (9 days) compared to other mushroom species (2-3 days). P. salmoneostramineus showed a vigorous growth in the fruiting body and the harvesting time required was just 5.67 days. It is clear from the result that there is no correlation between the rate of mycelia growth and pin appearance. The yield varied significantly due to the effect of mycelial growth on the substrate. The highest first flush and number of fruiting bodies was achieved in the yellow oyster followed by P. ostreatus grey and P. salmoneostramineus. In conclusion, sawdust and rice bran could be a promising substrate for linear mycelial growth of P. ostreatus species.